Governmentality and comic propaganda: Mighty Man, the black superhero of apartheid - Hammett, Daniel (Political geography, 2022)
Recent years have seen growing academic interest in the proliferation of a distinct genre of African superheroes. There is, however, a much longer – and at times, problematic – history of superheroes in and from Africa, a history often heavily infused with colonial and imperial ideology. Using the 1970s South African Mighty Man comic book series, this article highlights how popular culture and media can be used as covert and mundane tool of governmentality. Mighty Man can be understood as a technique of power deployed in service of the apartheid regime's philosophy of separate development, illustrating the use of popular culture as a technology of (colonial) governmentality. The landscapes, narratives and additional content of Mighty Man were used in efforts to instil and frame a conduct of conduct amongst Black subjects – both in accepting separate development and the apartheid government, and in framing the everyday practices and dispositions that would allow for governing at a distance by the white minority regime. Mighty Man provides a powerful example of state-commissioned, covert comic propaganda which was indelibly framed by government policy and an ambition to create and impose a set of values and ideals around the dispositions, behaviour and actions of Black subjects. Ultimately, Mighty Man embodied a segregationist fantasy in which the absence of non-Black characters both denied the possibility of inter-racial contact and normalised social and spatial segregation – as well as class-based aspirations – while simultaneously promoting the conduct of conduct amongst subjects that would maintain these divisions. Through the construction of moral township landscapes, the Mighty Man series not only sought to regulate the conduct of the colonised subject through the condemning of ‘immoral’ behaviours but also attempted to offer illusory hopes of aspiration and freedom.